2018
DOI: 10.1371/journal.pone.0195874
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of cultivable fungal endophytes in Paullinia cupana (Mart.) Ducke and bioactivity of their secondary metabolites

Abstract: Paullinia cupana is associated with a diverse community of pathogenic and endophytic microorganisms. We isolated and identified endophytic fungal communities from the roots and seeds of P. cupana genotypes susceptible and tolerant to anthracnose that grow in two sites of the Brazilian Amazonia forest. We assessed the antibacterial, antitumor and genotoxic activity in vitro of compounds isolated from the strains Trichoderma asperellum (1BDA) and Diaporthe phaseolorum (8S). In concert, we identified eight fungal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 241 publications
2
20
0
Order By: Relevance
“…In the present study, the susceptible genotype and, in general, the municipality of Manaus, were shown to have greater diversity. Similar results were observed in the seeds and roots of guarana studied in [ 42 ]. The authors related the richness of the susceptible genotype to the host vulnerability to microbial infections.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…In the present study, the susceptible genotype and, in general, the municipality of Manaus, were shown to have greater diversity. Similar results were observed in the seeds and roots of guarana studied in [ 42 ]. The authors related the richness of the susceptible genotype to the host vulnerability to microbial infections.…”
Section: Resultssupporting
confidence: 89%
“…The understanding of the factors guiding the microbial community of guarana is extremely important because it can elucidate how these microorganisms are structured in specific niches. In addition, the symbiotic interactions between endophytic fungi and guarana have been little explored [ 42 , 43 , 44 ]. The aim of this study was to identify the taxonomic composition of endophytes on leaves and seeds of guarana ( Paullinia cupana var.…”
Section: Introductionmentioning
confidence: 99%
“…control agents that fight the plant pathogens of S. suffruticosa, but also as new secondary metabolite resources with biological activities [63]. Of the 35 endophytic fungi, C. globosum, Fusarium sp.…”
Section: Plos Onementioning
confidence: 99%
“…The last endophytic fungus ( Purpureocillium lilacinum ) was among them specifically studied due to its potent antiprotozoal activity against Leishmania donovani (IC 50 0.174 μg mL -1 ); which was attributed to its production of purpureone, an ergochrome moiety [7]. It should be considered that different factors such as the plant organs, genotypic and geographic location influence the endophytic fungal community structure [8]. Endophytic fungi Curvularia sp.…”
Section: Introductionmentioning
confidence: 99%